The Influence of Presurgical Factors on the Rehabilitation Outcome of Patients Following Hip Arthroplasty. Issue 4 (July 2019) - Simões, João Lindo; Soares, Soraia; Sa-Couto, Pedro; Lopes, Carla; Magina, Daniela; Melo, Elsa; Voegeli, David; Bolhão, Isabel
Abstract: Purpose: The aims of this study were to evaluate the relationship between sociodemographic information, anthropometric values, clinical and presurgery factors, and length of stay (LOS) in older adult patients undergoing total hip arthroplasty (THA) and to predict which factors can delay the start of the rehabilitation program and increase the corresponding LOS. Methods: A prospective cohort study was conducted in an orthopedic inpatient unit with 40 patients undergoing THA. Findings: The Morse Fall Scale scores and pain intensity scores delayed the commencement of the rehabilitation program. Gender and social support were important determinants of LOS and rehabilitation outcome following THA. The weight of the lower limb without osteoarthritis followed by pain intensity and overweight patients also influenced LOS. Conclusions/Clinical Relevance: Functional outcomes after THA are variable, and the rehabilitation process is an important factor to regain their normal level of physical functioning. This factor can have an impact in the discharge of patients, in resource allocation and in health care of older adult patients.